Mini PCNL: A viable single stage treatment for pediatric nephrolithiasis in resource limited countries. Issue 3 (June 2021) - Rehman, Omer Farooq; Khan, Azhar; Harvey, Hannah; Umair, Musab; Murtaza, Badar; Nawaz, Muhammad; Iqbal, Zahoor
Summary: Introduction: There is increasing enthusiasm for the value of mini PCNL for pediatric stone clearance. In developing countries, it is important to arrange a single stage treatment as a significant proportion of patients do not comply with repeated treatments, such as SWL. Objective: To assess the safety, feasibility and outcomes of Mini PCNL in a pediatric cohort. Materials and methods: Retrospective analysis was performed of all paediatric patients undergoing Mini-PCNL at our institute between December 2016 and December 2019. Data was collected on stone size, stone clearance rate, complications, fluoroscopic exposure, mean procedural time and length of hospital stay. Follow up data included imaging to assess stone free status at 1 and 3 months postoperatively. Results: Mini PCNL was performed in 113 pediatric patients, a total of 135 procedures, accounting for bilateral disease in 22. The age range was from 1 to 14 years with a mean age of 8.45 ± 3.14 years. The mean stone burden was 2.1 ± 0.4 cm. Partial and complete staghorn stones were observed in 7 and 3 patients, respectively. The mean operative time was 63.8 ± 13.2 min (range: 25 min to 116min) and mean length of stay was 4.3 ± 2.2 days. Primary stone clearance was achieved in 91.1% (123 patients). Ancillary procedures were undertaken in 10 patients resulting in a secondary clearance rate of 97.0% (131 patients) at 3 months. Complications occurred in 16.3% (22 patients) using the modified Clavien Classification. Metabolic abnormalities were seen in 56.7% of patients with hypocitraturia and hypercalciuria being the most common abnormalities. Discussion: Our study reports a clearance rate of 91.1%, whereas, Zeng et al. documented a stone clearance rate of 80.4%. This contrast may be attributed to the difference in followup imaging protocols of the two studies and the energy source used for fragmentation. The incidence of complications with PCNL ranges from 10.6% to 36.3%, we found complications in 16.3% of our cohort. Our study is limited due to its retrospective design with a short follow-up protocol. Computed tomography being gold standard for qualitative and quantitative assessment of stone burden was not used in all patients to assess the preoperative stone size. Furthermore, postoperatively stone clearance was determined on the basis of ultrasound and x-ray films that could limit the accuracy of our stone clearance rate. Conclusion: Our study suggests that mini PNCL in pediatrics patients is an effective single stage treatment for definitive stone clearance with an acceptable complication risk. Summary Table Study variables. Summary Table Procedures (n) 135 Stone size (cm) 2.1 ± 0.4 Operative time (mins) 63.8 ± 13.2 Total Complication rate 22 patients (16.3%) Primary stone clearance 123 (91.1%) Secondary stone clearance 131 (97.0%) Ancillary Procedures (n) 10